2021
DOI: 10.3390/ma14195892
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Damage Characteristics of Asphalt Mixtures Using Fractional Rheology

Abstract: The mechanical behavior of asphalt mixtures at high stress levels are characterized by non-linear viscoelasticity and damage evolution. A nonlinear damage constitutive model considering the existence of creep hardening and creep damage mechanisms in the entire creep process is proposed in this study by adopting the fractional rheology theory to characterize the three-stage creep process of mixtures. A series of uniaxial compressive creep tests under various stresses were conducted at different temperatures to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…This method can simultaneously determine the retardation and relaxation spectra, which is more effective than the current approach. A fractional viscoelastic and damage constitutive relation of asphalt mixtures was proposed to characterize the three-stage creep process [21]. The model prediction results agreed well with the laboratory uniaxial compressive creep tests with different stress levels and temperatures.…”
supporting
confidence: 55%
“…This method can simultaneously determine the retardation and relaxation spectra, which is more effective than the current approach. A fractional viscoelastic and damage constitutive relation of asphalt mixtures was proposed to characterize the three-stage creep process [21]. The model prediction results agreed well with the laboratory uniaxial compressive creep tests with different stress levels and temperatures.…”
supporting
confidence: 55%
“…Moreover, the complexity of different high-molecular polymer modification systems may influence the internal structure of modified asphalt, thus influencing the rheological characteristics of asphalt. Rheological parameters in the linear viscoelasticity interval are independent of changes regarding stress and strain, and they are only related to the properties of the materials [32]. Therefore, linear viscoelasticity and dynamic rheological tests are very effective methods to elaborate on the influences of modifiers on the performances of modified asphalt and to study the influences of polymers on the viscoelasticity of asphalt.…”
Section: Rheological Properties Of Modified Asphaltmentioning
confidence: 99%
“…rough a large number of tests, it is found that non-aqueous reactive polyurethane grouting materials have similar viscosity characteristics to asphalt mixture. erefore, we searched the literature and relevant test procedures and referred to some test methods for the study of the rheological properties of asphalt mixture [25,[36][37][38]. e loading time for each step was tentatively determined to be approximately 1800 s (30 minutes).…”
Section: Creep Test Schemementioning
confidence: 99%